A Pitfall of Falsely Elevated ACTH: A Case Report and Literature Review - Yung-Yu Yang MD; Chih-Chun Kuo MD; Ming-Hsun Lin MD; Chun-Yung Chang MD; Chang-Hsun Hsieh MD; Chieh-Hua Lu MD (SAGE Publishing, 2022)
A 35-year-old woman with unintentional weight gain, hyperpigmentation of bilateral palms, and general fatigue was initially suspected of Cushing's syndrome or adrenal insufficiency based on the isolated elevation of the plasma adrenocorticotropic hormone (ACTH) level (113.0 pg/mL) in the Siemens ACTH Immulite assay (ACTH [Immulite]). However, both of the diagnoses were excluded by screening tests including the overnight dexamethasone suppression test, the 24-hour urinary free cortisol excretion, and the ACTH stimulation test in spite of the consistent elevation of the plasma ACTH levels. We speculated that the existence of the immunoassay interference may be the underlying cause because the plasma ACTH level analyzed by the CIS Bio International ELSA-ACTH immunoassay (ELSA-ACTH) was within the normal range. After reviewing our case and several reported cases of falsely elevated plasma ACTH levels, we conclude that when discrepancy between clinical symptoms and laboratory measurements exists, medical practitioners ought to rely on formal diagnostic criteria rather than misleading laboratory results to avoid misdiagnosis or even unnecessary invasive testing and procedures. In addition, current methods for investigation and elimination of immunoassay interferences should be applied with caution due to variable efficacy and inevitable deviations.